Longitudinal variation of water quality in Sungai Jarum catchment - linking ecology with hydrology for reservoir management - Wan Ruslan Ismail,; Ku A’edah Ku Hashim, (Environmental Management Society, Malaysia, 2004)
In recent years, human activities, such as urbanization and agriculture, have been blamed for the degradation of water quality in many developing countries. Rivers draining agricultural land are susceptible to diffused or non-point source pollution. A study was conducted in Timah Tasoh catchment areas with the aim to investigate the effect of land use activities and eutrophication of the Timah Tasoh reservoir. A water quality monitoring programme was carried out from January 2001. This paper, however, focuses on the longitudinal variation of water quality parameters of Sungai Jarum as one of the two major water sources for the reservoir. The study was carried out from July to December 2001. Most physical parameters (temperature, dissolved oxygen, pH, conductivity, total dissolved solids, TDS; turbidity) and nutrients varied between stations along the river. The general trend was that the water quality was getting better approaching the reservoir, where nutrient contents decreased longitudinally from its sources in the upper catchment to the reservoir. A reduction of almost 80% and 90% was observed for nitrogen and phosphorus, respectively at Tasoh, and a further reduction from Tasoh to the reservoir. Sedimentation and nutrient uptake by plant along the river corridor and in the littoral zones is the most probable cause for the reduction in nutrient contents and help maintaining good water quality of the reservoir